Hematologic Malignancies Are Associated with Adverse Perioperative Outcomes following Total Knee Arthroplasty - Newman, Jared M.; Wagner, Timothy C.; Naziri, Qais; North, W. Trevor; Navale, Suparna M.; Klika, Alison K.; Barsoum, Wael K.; Higuera, Carlos A. (The Journal of Knee Surgery, 2018)
The treatment of hematologic malignancies has advanced over the years, resulting in an improved survival of patients. As a result, these patients may be a part of the increasing population requiring total knee arthroplasty (TKA); however, they might be at a higher risk of adverse perioperative outcomes. The purpose of this study was to determine the perioperative outcomes (complications, length of stay [LOS], and costs) of patients with hematologic malignancies following TKA. This study used the Nationwide Inpatient Sample (NIS) to identify patients who underwent TKA in the United States from 2000 to 2011. Patients diagnosed with any hematologic malignancy (N = 24,714) were then stratified by Hodgkin's disease (N = 791), Non-Hodgkin's lymphoma (N = 7,096), plasma cell dyscrasias (N = 1,621), leukemia (N = 8,005), myeloproliferative disease (N = 5,746), and/or myelodysplastic syndromes (N = 1,608) for determining the complications that occurred during admission. Propensity matching was performed for demographics, hospital characteristics, and comorbidities, which yielded 24,491 patients with any hematologic malignancy and 24,458 control patients. Additionally, propensity matching was performed for the hematologic malignancy subtypes. Multivariable regression models were used to analyze the surgical and medical complications, LOS, and costs. The annual frequency of THA in patients with any hematologic malignancy increased from 2000 to 2011 (p < 0.0001). Hematologic malignancies were associated with an increased risk of any surgery-related complication (odds ratio [OR] = 1.31, p < 0.0001) and any general medical complication (OR = 1.38, p < 0.0001). Patients with any hematologic malignancy had increased odds of complications, including acute postoperative anemia (OR = 1.29, p < 0.0001), hematoma/seroma (OR = 1.65, p < 0.02), peripheral vascular disease (OR = 2.23, p = 0.046), deep venous thrombosis (DVT) (OR = 1.95, p = 0.02), and blood transfusion (OR = 1.61, p < 0.0001). Hematologic malignancies were associated with an increased incremental LOS (0.13 d, p < 0.0001) and an increased incremental cost ($788, p < 0.0001). Thus, we conclude that following TKA, patients with hematologic malignancies are at an increased risk of perioperative complications, longer LOS, and higher costs. The risk quantification for adverse perioperative outcomes in association with an increased cost may help design different risk stratification and reimbursement methods in such patients when undergoing TKA.
Keywords: total knee arthroplasty; hematologic malignancy; perioperative outcomes; length of stay; costs